Implementation of a digital narrative to facilitate the learning of fractions in primary school - Ochoa-Martínez, Oscar Luis; Díaz-Neri, Nadia Melina (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The objective of this research was to measure the impact of a digital narrative to facilitate the learning of fractions in elementary school children. The work had a quantitative approach and a deterministic sample was used, made up of 56 children distributed in two groups, who were studying in the 3rd year of primary education in the municipality of Durango, Mexico. The method was quasi-experimental, by applying pretest and posttest to an experimental group and a control group. The impact of the digital narrative was determined with the Student's t test for related samples and for independent samples. In the pretest, the experimental group showed greater difficulty in solving problems with fractional content, compared to the control group. After using the digital narrative, the experimental group improved their performance in the post-test, and there was no significant difference in the number of questions answered correctly, with respect to the control group. The latter indicates a positive and significant effect of digital storytelling on fraction learning.